Eating habits and nutritional knowledge among amateur ultrarunners - Kosendiak, Aureliusz; Król, Magdalena; Ligocka, Marta; Kepinska, Marta (Frontiers in Nutrition, 2023)
Many studies concerning the diet of physically active people refer to individuals who run; however, the importance of nutrition in professional and amateur sports plays a different role. This study aimed to evaluate the nutritional behavior and knowledge of amateur ultrarunners. This study involved a group of 308 respondents (89 women and 219 men) aged 18 to 65. It investigated the influence of the level of knowledge about nutrition, gender, education, and smoking on dietary food habits and eating frequency. The KomPAN questionnaire was used to determine the dietary habits, diet quality, lifestyle, and nutrition knowledge of ultramarathon runners. The nutrition knowledge influenced the eating habits and frequency of specific meals expressed as the Healthy Diet Index-10 (HDI-10) and Unhealthy Diet Index-14 (UDI-14). In women with sufficient knowledge about nutrition, lower HDI-10 scores were observed compared to those with a good level of knowledge, while men did not show a similar relationship. However, the effect of smoking on the frequency of food intake in men was noted. Interestingly, male smokers had a lower UDI-14 score than non-smokers. Depending on the level of knowledge, female and male ultrarunners more often or less frequently used selected food products. In turn, no effect of education on the frequency of consumption of specific foods was observed. Such different results are most likely caused by the specificity of the study group, which consisted of amateur runners. Additionally, the study looked at general eating habits, not those employed when preparing for marathons. In the future, more respondents should be surveyed, also taking into account nutrition during training.